THE IMPACT OF ROLE MODELS ON OUT OF TREATMENT AFRICAN-AMERICAN ADDICTS: AN INSIDE PERSPECTIVE - DiReda, James S. (European Scientific Journal, ESJ, 2014)
This article describes the findings of a qualitative study that examines the influence that positive role models in recovery from drug addiction had on a sample of 20 African-American male addicts. This article explains the effect of stigma and shame on drug addicts. It provides insight and understanding of what deters them from disclosing their drug use and seeking treatment, and explains the positive influence that recovering role models had on the addicts in this study in their decision to stop using drugs. These findings provide an insider perspective of drug addiction, and increase our knowledge of how to more effectively engage drug addicts. Data was collected using one-time taped interviews with 20 African-American male drug addicts. The findings suggest: (1) drug treatment was often perceived as ineffective, a last resort, or as punishment for addicts' behavior; (2) many respondents feared being stigmatized and shamed once they disclosed their drug use; (3) most reported having difficulty imagining their lives as different following treatment; (4) the strongest influence participants' reported was of former addicts acting as positive role models who engaged participants in a safe, non-judging manner around stopping their drug use. By exploring this topic we learned how this sample interpreted â€œentering treatment,â€ the barriers they encountered, and what influenced their decisionmaking process regarding treatment. This study helps recognize the benefits of using former drug addicts as role models to do outreach with active addicts due to their ability to understand and relate to this population.